Efectos en el rendimiento de la produccion de corcho al modificar el calibre de las planchas taponables - González Fernández, T; Al, D E Corcho; El, Modificar; Fernández, T González (Scientia gerundensis, 1989)
The main purpose of this paper is to analise the posible effects of a diminution on the caliber of the bottle-cork on the economic profitability of the Extremadura cork-oak forest. A reduction from 22 mm to 17 mm in the wine-bottle neck will supose an increment of 27% in the raw production of bottle-cork.
Keywords: Cork; Cork Production; cork-oak; wine bottle neck